ANALISIS AKUNTABILITAS, INDEPENDENSI, DAN PENGALAMAN KERJA AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR BPK PERWAKILAN KEPRI - Gea, Yarni Fantaria; Br Purba, Neni Marlina (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine the effect of auditor accountability, independence, and work experience on audit quality at the Riau Islands Representative Office of the BPK. The population in this study were all auditors who worked in the Riau Islands Representative Office of BPK as many as 40 auditors. The sampling technique used was the saturated sampling method, as many as 40 respondents. The data used are primary data and data analysis using multiple linear regression analysis to test the established hypothesis. This study shows the results that the accountability variable partially has a significant effect on audit quality at the Riau Islands Representative Office of the BPK. Meanwhile, the independence variable and auditor's work experience partially have no significant effect on audit quality at the Riau Islands Representative Office of the BPK. However, simultaneously the variables of accountability, independence, and work experience of auditors have a significant effect on audit quality at the Riau Islands Representative Office of the BPK.